Better not forget: On the memory of S&P 500 survivor stock companies - Klaus Grobys; Yao Han; James W. Kolari (Journal of Risk and Financial Management, 2023)
This study explores the dependency structure of S&P 500 survivor stocks. Using a hand-collected sample of stocks that survived in the S&P 500 since March 1957, we employ rescaled/range analysis to investigate survivors. First, we find nonlinearities in the return processes of survivor stocks due to Paretian tails. Second, the return processes of very long-lived outliers exhibit long-term memories with Hurst exponents that significantly exceed one half on average. Third, sample-split tests reveal that the memory on average has virtually not changed over time-that is, survivor stocks do not forget. Fourth, and last, the long-term memory of survivor stocks appears to be unrelated to their exposures to traditional asset pricing risk factors.
Keywords: G10; G12; G15; G19; 650; asset pricing; Hurst exponent; Paretian tails; S&P 500 index; survivor stocks